Kinerja Keuangan Perusahaan Industri Barang KonsumsiPada Masa Pandemi Covid-19 - Ni Luh Anik Puspa Ningsih; Made Pratiwi Dewi; Anak Agung Media Martadiani (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
Coronavirus disease 2019 (covid-19) has majority impacted the Indonesian economy. Various companies are required to be able to maximize the company's performance in the midst of this condition. Some important factors from within the company that interact in an effort to maximize company performance are the company's use of debt, liquidity and company size. This study aims to analyze the factors that have an impact on company performance as measured by profitability in the consumer goods industry in Indonesia. The sample of this research are 18 companies. By using path analysis, the results of this research are 1) firm size has a significant positive effect on firm performance, 2) firm size has a significant negative effect on capital structure, 3) liquidity has a significant negative effect on capital structure, 4) liquidity has a significant negative effect on firm performance, 5) capital structure has a significant negative effect on firm performance